2019
DOI: 10.1111/jan.14034
|View full text |Cite
|
Sign up to set email alerts
|

An intervention including the national early warning score improves patient monitoring practice and reduces mortality: A cluster randomized controlled trial

Abstract: Aims:To investigate the impact of the national early warning score on the frequency and the quality of vital sign registration and to study the association between protocol compliance and patient mortality. Design:We conducted a post hoc data analysis of a stepped wedge cluster randomized controlled trial (RCT) in six hospitals. Methods: All adult, non-pregnant patients admitted to 24 wards were included. The intervention comprised an observation protocol using the national early warning score combined with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 21 publications
2
19
0
8
Order By: Relevance
“…In our results, the high-risk cutoff points show that, globally, for the NEWS2 scale, 7 points is where the best joint sensitivity and specificity is obtained-a score that reached 8 points for the SARS-CoV-2 positive population. This fact is in accordance with results from other studies carried out on different populations and health settings [27,45,46].…”
Section: Discussionsupporting
confidence: 93%
“…In our results, the high-risk cutoff points show that, globally, for the NEWS2 scale, 7 points is where the best joint sensitivity and specificity is obtained-a score that reached 8 points for the SARS-CoV-2 positive population. This fact is in accordance with results from other studies carried out on different populations and health settings [27,45,46].…”
Section: Discussionsupporting
confidence: 93%
“…[1][2][3][4][5][6] Underlying causes such as sepsis, acute coronary syndrome and pulmonary embolism may be treated promptly with early detection. [7][8][9][10][11][12] Such delays have been highlighted in the 2018 National Confidential Enquiry into Patient Outcome and Death Common Themes and Recommendations report. 13 In response to the need for early detection, the National Early Warning Score was introduced by the Royal College of Physicians in 2012 with further updates in 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to implementation of a PEW system, there is signi cant variation (25 to 88%) in the frequency of observations 1,2,15 . Two randomised control trials 2,16 and a systematic literature review 17 have shown that following implementation of a PEW system, there is demonstrable improvement in observation performance and patient mortality. It has also been shown that effective identi cation, rather than response team attendance, is associated with these improved outcomes 18,19 .…”
Section: Discussionmentioning
confidence: 99%